The arrival of the Hungarians in the Carpathian Basin as seen by medieval Hungarian chroniclers - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2007)
The arrival of the Magyars in the Carpathian Basin at the end of the 9th century was one of the most important events in the history of Central Europe and found lasting reflection in both oral tradition and medieval Hungarian historiography. The aim of this article is to show how Hungarian chroniclers from the 11th to the 14th century presented this process of settlement and the events that accompanied it. The source material consists of Hungarian chronicles, ranging from the lost Gesta Ungarorum to the works of Anonymus, notary of King Béla III, the chronicle of Simon of Kéza. In addition, oral traditions preserved in Hungarian folklore, Byzantine and Western European sources were also used. The research method is a comparative analysis of narrative accounts appearing in various editions. The author presented the mechanisms of creating narratives of a legitimising nature – they ensured the continuity of power, explained the Magyars' right to new lands and placed their history in a broader European context. Hungarian chroniclers created a canonical image of the Magyar settlement in the Carpathian Basin, combining elements of oral tradition with erudite inspirations. These narratives shaped historical memory and legitimised the socio-political order of medieval Hungary.